Expert organisations with “challenging” and “complex” service users: Representation in English and Welsh autism charity reports and accounts - Helen Abnett; Kathryn Williams; Willow Holloway; Aimee Grant (PLoS ONE, 2025)
The language and imagery used in Autism charities’ communications influences societal understanding of, and attitudes towards, Autistic people. This, in turn, shapes perceptions of whether and how the disabling barriers in society experienced by Autistic people can and should be addressed. Yet, to date, there has been minimal exploration of this discourse employed by Autism charities. We, an Autistic-majority team of researchers, used critical reflexive thematic analysis to examine the language and imagery used in the Trustees’ Annual Reports and Accounts of 11 large English and Welsh Autism charities. Representation within these reports emphasises adversities associated with Autism, and the language chosen to portray Autistic people largely describes Autism as an impairment. In contrast, charities represent themselves as the solution to the ‘problem’ of Autistic people, and thus deserving of increased resources and funding. Government is largely depicted as ineffective and deficient. We argue that these Autism charities are thereby upholding – rather than challenging – the disabling barriers in society experienced by Autistic people. For Autistic charities to better represent Autistic people and improve wider societal understanding of Autism, there is a need for more positive portrayals that challenge the ‘charity saviour’ trope in charity communications.